2008
DOI: 10.1002/psp.479
|View full text |Cite
|
Sign up to set email alerts
|

Dynamics of ethnic residential segregation in Göteborg, Sweden, 1995–2000

Abstract: Most explanatory frameworks within segregation research interpret patterns of ethnic residential segregation as the result of how members of different ethnic groups have moved (or not moved) within the city and to the city from the surrounding world. Yet, few attempts have been made to proceed beyond relatively static accounts based on descriptions and analysis of patterns of segregation, to address more directly the dynamics behind the patterns. In this article, a longitudinal, individual‐based data‐set is us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
40
0
1

Year Published

2010
2010
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(49 citation statements)
references
References 21 publications
8
40
0
1
Order By: Relevance
“…Out‐migration from ethnic areas could also lead to new forms of spatial segregation outside gateway cities (Zelinsky and Lee, 1998; Ellis and Goodwin‐White, 2006). For example, ethnic minorities could prefer minority‐rich destinations because social networks and institutional resources are more likely to flourish in large, viable ethnic communities that allow easier access to employment and housing information for its members (Hou, 2007; Bråmå, 2008). For example, Li (1998) introduced the ‘ethnoburbs’ concept to characterise suburban ethnic neighbourhoods with vibrant ethnic economies for mainly white‐collar workers that are emerging in one of the main immigration centres in the US (Los Angeles).…”
Section: Theoretical Insights Into Ethnic Minority Dispersionmentioning
confidence: 99%
“…Out‐migration from ethnic areas could also lead to new forms of spatial segregation outside gateway cities (Zelinsky and Lee, 1998; Ellis and Goodwin‐White, 2006). For example, ethnic minorities could prefer minority‐rich destinations because social networks and institutional resources are more likely to flourish in large, viable ethnic communities that allow easier access to employment and housing information for its members (Hou, 2007; Bråmå, 2008). For example, Li (1998) introduced the ‘ethnoburbs’ concept to characterise suburban ethnic neighbourhoods with vibrant ethnic economies for mainly white‐collar workers that are emerging in one of the main immigration centres in the US (Los Angeles).…”
Section: Theoretical Insights Into Ethnic Minority Dispersionmentioning
confidence: 99%
“…Residential mobility and spatial dispersion are major phenomena, even in ethnically concentrated neighbourhoods (Simpson, 2004(Simpson, , 2005(Simpson, , 2007Simpson et al, 2008). In France, Sweden, Norway and the Netherlands, considerable spatial mobility has been documented, often into neighbourhoods with better characteristics for immigrants of all origins (Bråmå, 2008;Musterd and van Kempen, 2009;Pan Ké Shon, 2010;Andersson et al, 2010), thus suggesting an ongoing, progressive incorporation process. …”
mentioning
confidence: 99%
“…By comparing different regions in the Netherlands, Zorlu and Mulder (2008) show how recent immigrants are located in areas where deprivation indicators, such as substandard housing, are high. In the case of Sweden, Bråmå (2008) and Åslund (2005) also introduce a number of housing market conditions. In short, for both of these countries, it is shown that, in general, new immigrants live in very different housing conditions from those of the native population.…”
Section: Housing Marketmentioning
confidence: 97%
“…Among the authors using spatially referenced data, only one researcher uses intra-metropolitan spatial data to analyze the dynamics of immigrant settlement patterns (Bråmå 2008). To our knowledge, no study has as yet introduced spatial effects to explain the growth of the immigrant population within urban areas.…”
Section: Introductionmentioning
confidence: 99%